The influence of teacher variables on climate change science literacy of Geography teachers in the Western Cape, South Africa - Anyanwu, Raymond Ndubisi; Grange, Lesley Le (International Research in Geographical and Environmental Education, 2017)
Teachers play an important role in promoting climate change literacy in schools, but not much is known about which teacher characteristics significantly influence Geography teachers’ climate change science literacy. The purpose of this study is to determine the influence of teachers’ characteristics such as gender, age, qualification, specialisation, experience, and teaching grade on Geography teachers’ literacy about climate change science. The study uses a quantitative research approach on questionnaire application. Statistical analysis of data gathered from 194 high school Geography teachers from the Western Cape Province using a 15-item Climate Change Science Literacy Questionnaire (CCSLQ) revealed that gender, age, teaching experience, and teaching grade significantly influenced Geography teachers’ literacy about climate change science, while qualification and specialisation did not.
Keywords: C:South Africa; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change science literacy; oa:keyword:geography teachers; oa:sdg:13 Climate action; oa:topic:T10072 Enhancing Science Education through Inquiry and Argumentation; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Climate change science: The literacy of Geography teachers in the Western Cape Province, South Africa - Anyanwu, Raymond Ndubisi; Grange, Lesley Le; Beets, Peter (South African Journal of Education, 2015)
One of the universal responses to tackling global climate change is teaching climate change concepts at all levels of formal education. This response requires, among other things, teachers who are fully literate about climate change science, so that they can explain the concepts underlying the causes, impacts and solutions of climate change as accurately as possible to learners. The main intention of this study was to understand high school Geography teachers’ levels of knowledge about climate change science. A 15-item, criterion-referenced, multiple-choice Climate Change Literacy Questionnaire with a reliability coefficient of 0.74 using the Guttman’s spit-half test was administered to 194 high school Geography teachers in the Western Cape Province of South Africa. Data collected were analysed with the Pearson’s Chi-square test and One-Way Analysis of Variance (ANOVA). The results showed that the majority of the participants demonstrated significantly high literacy levels in climate science, with their literacy levels higher in climate processes and causes of climate change than climate change impacts and solutions. Misconceptions were found in all three categories of climate change science as represented in the survey instrument. These findings suggest that teacher educators and policymakers should improve professional development programmes and support interventions in teacher knowledge and understanding of climate change concepts, so as to enhance climate change education in schools.Keywords: climate change education; climate change misconceptions; climate change science literacy; Geography teachers; survey research
Keywords: C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:climate change science; oa:keyword:geography teachers; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12904 Agricultural Education and School Gardening Research; oa:topic:T13435 Human Attitudes and Interactions with Animals and Plants; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found